Love and Money by Parental Matchmaking: Evidence from Urban Couples in China - Huang, Fali; Jin, Ginger Zhe; Xu, Lixin Colin (American Economic Review, 2012)
Parental involvement in marriage matchmaking may distort the optimal spouse choice because parents are willing to substitute love for money. The rationale is that the joint income of married children can be shared among extended family members more easily than mutual attraction felt by the couple themselves, and as a result, the best spouse candidate in the parents' eyes can differ from what is optimal to the individual, even though parents are altruistic and care dearly about their children's welfare. We find supporting evidence for this prediction using a unique sample of urban couples in China in the early 1990s.